Coercion to Conversion : Push and Pull Pressures on Custom Land in Vanuatu - Haccius, Justin (World Bank, Washington, DC, 2018)
This paper describes some features of custom landholding. It evaluates elements of the process by which custom land is converted into registerable form, and considers how the judicial system is placed to resolve disputes involving custom landholders in a context where the framework for the recognition of custom is under-developed. Certain commentators argue that custom landholding is inherently incompatible with economic development. Others disagree pointing to success stories and arguing that a purely economic analysis dismisses the benefits, also inherent in custom landholding, of community and culture. Wherever one stands on this debate, what is clear is that the process of converting custom land into registered leasehold is fraught with dispute, disillusionment and controversy. The current process is sharply tilted toward the structures of the formal system and the interests of those who have access to that system with the result that: (i) custom landholders are often excluded from equitable participation in the development of their land, and (ii) attempts to use the legal system to respond to these problems are frustrated.